Neuroprotective and Neurotherapeutic Effects of Tetrahedral Framework Nucleic Acids on Parkinson’s Disease in Vitro - Cui, Weitong; Zhan, Yuxi; Shao, Xiaoru; Fu, Wei; Xiao, Dexuan; Zhu, Junyao; Qin, Xin; Zhang, Tianyi; Zhang, Mei; Zhou, Yi; Lin, Yunfeng (ACS applied materials & interfaces, 2019)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by a series of progressive motor disorders. PD is caused by dysfunction of basal ganglia, decrease of dopaminergic neurons in substantia nigra, and abnormal accumulation of Lewy bodies and Lewy neurites. Antiparkinsonian agents, which are currently used for treatment of PD, exhibit unsatisfactory effects on disease control. In recent years, tetrahedral framework nucleic acids (TFNAs) have been considered as multifunctional nanomaterials, and their scope of application has been extended to a wide range of areas. In previous studies, TFNAs were shown to exert positive effects on various cell types in processes such as cell proliferation, cell differentiation, and apoptosis. In the present study, we explored the role of TFNAs in the treatment and prevention of PD in vitro and elucidated its underlying mechanisms of action. On the basis of the experiments conducted, we demonstrated that TFNAs could inhibit and repair the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced apoptosis of PC12 cells through decreasing the accumulation of α-synuclein, one of the characteristic biomarkers of PD. Genes and proteins related to the AKT/PI3K signaling and mitochondrial apoptotic pathways were examined to further support this finding. Most importantly, TFNAs exhibited unexpected neuroprotective and neurorestorative effects on PC12 cells, providing a novel approach for reducing the neuropathological changes caused by PD.